Case Report and Literature Review of a Pathologic Mandibular Fracture from Metastatic Esophageal Adenocarcinoma - Daniel C. O’Brien; Garrett Jones; Maggie Yell; Jason McChesney (Case Reports in Otolaryngology)
Distant metastasis to the jaws, including the maxilla or mandible, is very rare. Although the mandible is the preferred sight of these rare metastases, it is extremely rare for oral cavity malignancies to present as pathological mandibular fractures. Here, we present a case of esophageal adenocarcinoma metastasizing to the mandible, and the first reported case presenting with a pathological mandibular fracture secondary to esophageal adenocarcinoma. We also review the 9 other reported cases of metastatic esophageal adenocarcinoma to either the maxilla or mandible.